2004
DOI: 10.1021/jf035412g
|View full text |Cite
|
Sign up to set email alerts
|

Furfuryl Ethyl Ether:  Important Aging Flavor and a New Marker for the Storage Conditions of Beer

Abstract: Recently, it was reported that furfuryl ethyl ether is an important flavor compound indicative of beer storage and aging conditions. A study of the reaction mechanism indicates that furfuryl ethyl ether is most likely formed by protonation of furfuryl alcohol or furfuryl acetate followed by S(N)2-substitution of the leaving group by the nucleophilic ethanol. For the reaction in beer, a pseudo-first-order reaction kinetics was derived. A close correlation was found between the values predicted by the kinetic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 29 publications
4
36
0
Order By: Relevance
“…The elemental mappings showed fairly homogeneous metal dispersions; no particles of bulk zirconia or alumina were observed, which is consistent with the PXRD studies. The EDS analyses of (Zr) SSIE -beta and (ZrAl) SSIE -beta indicated that they possess similar atomic ratio Si/(Zr+Al) (16)(17)(18)(19) (Table 2), which is consistent with the fact that the molar amounts of Zr or (Zr+Al) added to deAl-beta were the same for the two materials ( Table 1). The atomic ratio Al/Zr was higher for (ZrAl) SSIE -beta than (Zr) SSIE -beta (1.2 and 0.03, respectively), and the Si/Al ratio was much lower for (ZrAl) SSIE -beta (35 compared to 588 (Zr) SSIE -beta), which is consistent with the fact that (ZrAl) SSIE -beta was obtained via SSIE for both Zr and Al.…”
Section: Beta Type Materialssupporting
confidence: 66%
See 1 more Smart Citation
“…The elemental mappings showed fairly homogeneous metal dispersions; no particles of bulk zirconia or alumina were observed, which is consistent with the PXRD studies. The EDS analyses of (Zr) SSIE -beta and (ZrAl) SSIE -beta indicated that they possess similar atomic ratio Si/(Zr+Al) (16)(17)(18)(19) (Table 2), which is consistent with the fact that the molar amounts of Zr or (Zr+Al) added to deAl-beta were the same for the two materials ( Table 1). The atomic ratio Al/Zr was higher for (ZrAl) SSIE -beta than (Zr) SSIE -beta (1.2 and 0.03, respectively), and the Si/Al ratio was much lower for (ZrAl) SSIE -beta (35 compared to 588 (Zr) SSIE -beta), which is consistent with the fact that (ZrAl) SSIE -beta was obtained via SSIE for both Zr and Al.…”
Section: Beta Type Materialssupporting
confidence: 66%
“…Besides FA, various useful bio-products, such as alkyl furfuryl ethers (FEs), levulinate esters (LEs), angelica lactones (AnLs), levulinic acid (LA), and -valerolactone (GVL) can be produced from Fur (Scheme 1) [13][14][15]. For example, FEs are used as blending components of gasoline [16,17] and as flavours [18,19]. LEs are useful chemical intermediates for producing coatings, resins and flavour preparations [20,21], anticancer agents, pesticides and insecticides [22].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the test indicated acetoin production by S. marcescens MG1 and also by its swrI mutant in the presence of 10 M C 4 -HSL, but not in its absence (data not shown). A more specific analysis of 2,3-butanediol and its precursors diacetyl and acetoin by gas chromatography coupled to mass spectrometry was performed as previously described (15). Briefly, gas chromatography was performed by using a Fisons GC 8000 gas chromatograph (Fisons, Mainz, Germany) equipped with a Chrompack CP-WAX-52-CB column (Varian, Palo Alto, CA), and total ion mass chromatograms were obtained with a Fisons MD 800 quadrupole mass spectrometer (Fisons, Mainz, Germany) and analyzed using the Masslab software program (ThermoQuest, Manchester, United Kingdom) for identification and quantification of volatiles.…”
Section: Vol 188 2006 Notesmentioning
confidence: 99%
“…It can be converted to the bio-products furfuryl alcohol (FA), furfuryl alkyl ethers (FEs), levulinate esters (LEs), levulinic acid (LA), angelica lactone isomers (AnLs) and -valerolactone (GVL) [2][3][4] (Scheme 1), useful in different sectors of the chemical industry. FA, industrially produced via hydrogenation of Fur, is used in the foundry 3 industry [5], and FEs are used as blending components of gasoline [6,7] and as flavour compounds [8,9]. LEs are used as oxygenate fuel additives [10][11][12], solvents, and to produce plasticizers and flavouring agents [13][14].…”
Section: Introductionmentioning
confidence: 99%